PENGARUH BIMBINGAN KELOMPOK MENGGUNAKAN PERMAINAN ULAR TANGGA TERHADAP STRES AKADEMIK SISWA DI SMK PGRI PANGKALAN BALAI - Amelia, Mita; Tanjung, Romi Fajar (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Academic stress is a common problem faced by students, especially at the secondary education level. This study aims to evaluate the effectiveness of group guidance services using snakes and ladders games in reducing academic stress of students in class XI Business Service Office Management (MPLB) at SMK PGRI Pangkalan Balai. The method used in this research is an experiment with a One Group Pretest-Posttest design. The research sample consisted of 10 students who experienced academic stress. Data were collected through pretest and posttest which were processed by descriptive statistical analysis, normality test, and hypothesis testing using paired sample t-test. The results showed that there was a significant decrease in students' academic stress level, with the average academic stress score decreasing from 85.50 in the pretest to 74.20 in the posttest. The hypothesis test results show a significance value of 0.007 (<0.05), which indicates a significant effect of group guidance with snakes and ladders games on reducing academic stress. This study concludes that group guidance with snakes and ladders game is effective in reducing students' academic stress, creating a fun atmosphere, and increasing students' interaction and involvement in the guidance process which can reduce the academic stress they feel.